The limits of discretion in the investigation and prosecution of war crimes at the international level: The Mavi Marmara saga - Billis, Emmanouil (Bergen journal of criminal law & criminal justice, 2022)
The article deals with the basic criteria involved in the selection of situations to be investigated and cases to be prosecuted before the International Criminal Court. These are examined in light of the goals of international criminal justice and the structural and evidentiary difficulties encountered by judicial mechanisms of international mission and composition. The analysis focuses on the limits of prosecutorial discretion at the level of international criminal justice. The Mavi Marmaraship incident is used hereto as a key point of reference.